Phenolic Characterization of a Purple Maize (Zea mays cv. “Moragro”) by HPLC–QTOF-MS and Study of Its Bioaccessibility Using a Simulated In Vitro Digestion/Caco-2 Culture Model - Rodriguez, Marianela Desireé; Monsierra, Luisina; Mansilla, Pablo Sebastián; Pérez, Gabriela Teresa; De Pascual-Teresa, Sonia (2024)
Fil: Rodriguez, Marianela Desireé. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias; Argentina.